A new species of genus Psilocladia Warren from India, bridging the boundaries of Africa and Asia (Lepidoptera: Geometridae: Ennominae) - Singh, Manpreet; Lenka, Rajesh; Chatterjee, Pallab; Singh, Navneet (Zootaxa, 2025)
In the present manuscript, we describe a new species i.e., Psilocladia indica M. Singh, Lenka & N. Singh, sp. nov., from India and diagnose with its close congeners based on wing pattern and genitalia. Psilocladia indica sp. nov. is the fifth species of the genus. This study also reports Psilocladia Warren, 1898, a genus hitherto known only from Africa, for the first time from Asia. Psilocladia is closely similar to an African genus, Xenimpia Warren, 1895 and an Oriental genus Krananda Moore, 1868. The diagnostic attributes are explained and illustrated herein. Additionally, global checklist and identification key to all the species of the Psilocladia are provided.